Assessment of quality of prescription by dental students - Cariacy Silva de MOURA; Janeth Oliveira Silva NAVES; Eduardo Barbosa COELHO; Erica Negrini LIA (University of São Paulo, 2014)
Objective: The main objective of this study was to evaluate changes in prescribing pattern of Dentistry students throughout academic course. Methods: A case of non-complicated dental extraction was presented to all students that had completed their pharmacology coursework (from 4th semester to the last semester). The students were grouped according to year of study and were asked to prescribe paracetamol for pain control. A maximal score of 5 points was calculated from three subscores for identification of professional and patient (1.0 point), drug concentration, dosage, and quantity (1.5 points); and drug information, instructions, and warnings (2.5 points). The data were expressed as medians [95% confidence intervals (CIs)] and were compared using the Kruskal-Wallis test followed by Dunn's post hoc test. A p<0.05 value was considered statistically significant. A total of 92 students participated the study (2nd year, N=12; 3rd year, N=32; 4th year, N=28; 5th year, N=20). Results: The quality of prescription showed improvement between 2nd-year students [2.0 (1.5-2.5)] and 4th-year students [3.2 (2.9-3.5), p<0.05]; 4th- and 5th-year students [3.6 (3.5-3.8)] performed similarly. Lack of information about pharmacological treatment, side effects, and administration route were the major deficiencies observed. Conclusion: Although Dentistry students present a general improvement in their prescribing performance, deficiencies remain even in advanced students. The data suggest that the teaching of good prescription practices should extend throughout the later phases of preprofessional dental education.